Advertisement and release calls in Neotropical toads of the Rhinella granulosa group and evidence of natural hybridization between R. bergi and R. major (Anura: Bufonidae) - Guerra, Cecilia; Baldo, Diego; Rosset, Sergio; Borteiro, Claudio; Kolenc, Francisco (Zootaxa, 2011)
The Rhinella granulosa group currently includes 12 species distributed eastern to the Andes, from Panama to central Argentina. We studied bioacoustic features of the advertisement calls in seven of these species: Rhinella azarai, R. bergi, R. centralis, R. dorbignyi, R. fernandezae, R. major, and R. merianae. In addition, we analyzed the release calls of R. azarai, R. bergi, R. dorbignyi, and R. fernandezae. The advertisement calls consisted of long trills, composed by notes with a variable pulse number (2–8) that was characteristic of each species. The release calls consisted of a single note, pulsed or not. Both advertisement and release calls clearly varied between species, except for R. dorbignyi and R. fernandezae. The study of specimens sharing exosomatic characters with R. bergi and R. major from a syntopy area, which presented intermediate spectral and temporal call parameters, confirmed natural hybridization between these two species.